Meet the Board of ChemistryOpen: Sheshanath V. Bhosale - Jangale, Asha D. (ChemistryOpen, 2019)
Sheshanath V. Bhoslae [Image: see text] received his PhD from Freie University Berlin (Germany) in supramolecular chemistry under the supervision of Prof. J. H. Fuhrhop in 2004. He then pursued his postdoctoral studies with Prof. S. Matile at University of Geneva (Switzerland) under the auspices of a Roche Foundation Fellowship. This was followed by a stay at Monash University (Australia) for 5 years as an ARC‐APD Fellow. He worked at RMIT University, Melbourne (Australia) for 6 years as ARC‐Future Fellowship. Currently, Prof. Bhosale is working at the Department of Chemistry, Goa University (India) as a UGC‐FRP Professor, His research interests lie in the design and synthesis of π‐functional materials, especially small molecules, for sensing, biomaterials, and supramolecular chemistry applications. So far, Prof. Bhosale has produced 185 research articles and his work has been cited more than 4400 times, giving him an h‐index of 32. He currently serves as an active Editorial Board member for ChemistryOpen.